2003
DOI: 10.1111/j.1349-7006.2003.tb01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor response to chemotherapy: The validity and reproducibility of RECIST guidelines in NSCLC patients1

Abstract: We investigated the validity and inter-criteria reproducibility between RECIST (Response Evaluation Criteria in Solid Tumors) guidelines and WHO (World Health Organization) criteria, considering the decrease in patient numbers resulting from inclusion of the minimum lesion size criterion introduced in RECIST guidelines. RECIST guidelines are based on unidimensional measurement and exclusion of small lesions from measurement. The aims of the study were to examine: (1) the effect of the minimum lesion size crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 9 publications
1
42
0
Order By: Relevance
“…It has been previously reported that when surgery is used as an upfront treatment modality in patients with stage IIIA NSCLC, up to 30% of patients will have incomplete resection leaving behind macroscopic disease. 7 The 5-year survival rate for patients with incomplete resections is < 5%. [7][8][9][10] However, even in patients who can undergo complete resections, the risk of systemic disease is significant and the overall survival without adjuvant therapy at 5 years is only 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that when surgery is used as an upfront treatment modality in patients with stage IIIA NSCLC, up to 30% of patients will have incomplete resection leaving behind macroscopic disease. 7 The 5-year survival rate for patients with incomplete resections is < 5%. [7][8][9][10] However, even in patients who can undergo complete resections, the risk of systemic disease is significant and the overall survival without adjuvant therapy at 5 years is only 10%.…”
Section: Discussionmentioning
confidence: 99%
“…7 The 5-year survival rate for patients with incomplete resections is < 5%. [7][8][9][10] However, even in patients who can undergo complete resections, the risk of systemic disease is significant and the overall survival without adjuvant therapy at 5 years is only 10%. 8 Furthermore, it is very difficult to administer adjuvant therapy after major surgery, with patient compliance limiting completion of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation was conducted to determine the total cost an intervention would incur the IMSS per patient over the entire duration of second-line GIST treatment. Treatment costs were collected from the start of treatment until the documentation of tumour progression (Park et al, 2003;Watanabe et al, 2003). Further, patient data was investigated for a maximum of 5 years (referred to as the 5-year temporal horizon) so MC would be a true cost estimate of GIST care with a specific treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for approximately 80% of all lung cancers, and adenocarcinoma (AC) comprises about 50% of NSCLC (Jemal et al, 2007). Although platinum-based chemotherapy regimens improve the survival of patients with advanced NSCLC, resistance to chemotherapeutic agents is a major problem (Watanabe et al, 2003, Perng et al, 2008. In clinical practice, the chemotherapy response is variable among individuals.…”
Section: Introductionmentioning
confidence: 99%